Doing Business in the Arab World 2012 : Doing Business in a More Transparent World - International Finance Corporation; World Bank (Washington, DC, 2013)
Doing Business in the Arab world 2012 is a regional report drawing on the global Doing Business project and its database as well as the findings of Doing Business 2012, the ninth in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Doing Business presents quantitative indicators on business regulation and the protection of property rights that can be compared across 183 economies, from Afghanistan to Zimbabwe, and over time. A clear message emerging from the political transformation of the Arab world is the demand for more inclusive, broad-based growth that creates opportunity for many who have not shared in the benefits of private sector development in the past. In most Arab economies the unemployment rate remains in double digits, and the majority of the unemployed are under the age of 30. Policies focused on promoting inclusive growth, creating incentives for the private sector to create more good jobs and improving governance can increase employment opportunities for young people in the region.